2015
DOI: 10.1177/147470491501300208
|View full text |Cite
|
Sign up to set email alerts
|

The Unholy Trinity: The Dark Triad, Sexual Coercion, and Brunswik-Symmetry

Abstract: Psychopathy, Narcissism, and Machiavellianism (the Dark Triad) have each been hypothesized as predictors of socially deviant behavior including sexual coercion, but the three traits also covary significantly with one another. The purpose of this study was to examine several alternative Multisample Structural Equation Models (MSEMs) exploring the relations between the Dark Triad and Sexually Coercive Behavior, testing whether any or all of the three specific "Dark Personality" traits uniquely contributed to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 51 publications
(85 reference statements)
2
42
0
1
Order By: Relevance
“…For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a). For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a). For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a).…”
mentioning
confidence: 99%
“…It has been suggested that the Dark Triad traits reflect a meaningful and evolutionary relevant latent construct (Jonason et al, 2009), and idea that has received support from overseas researchers (Bertl, Pietschnig, Tran, Stieger, & Voracek, 2017) and those parsing the shared and unique variance using structural equation modelling in relation to important outcomes like sexual assault (Figueredo et al, 2015;Jonason, Girgis, & Milne-Home, 2017). This has both conceptual and measurement implications.…”
mentioning
confidence: 99%
See 3 more Smart Citations